2018
DOI: 10.1080/17474124.2018.1517044
|View full text |Cite
|
Sign up to set email alerts
|

Microbial modulation of the gut microbiome for treating autoimmune diseases

Abstract: Many studies have shown the relationship between autoimmune diseases and the gut microbiome in humans: those with autoimmune conditions display gut microbiome dysbiosis. The big question that needs to be addressed is if restoring eubiosis of the gut microbiota can help suppress the autoimmune condition by activating various immune regulatory mechanisms. Inducing these self-healing mechanisms should prolong good health in affected individuals. Area covered: Here, we review the available clinical and preclinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 125 publications
2
33
0
1
Order By: Relevance
“…These and previous studies in spondyloarthritis and rheumatoid arthritis reflect the growing interest of researchers to the role of the gut microbiome in shaping local and systemic immune responses and in pathogenesis of various rheumatic diseases 3. We agree with Deshayes et al that in the future microbiome engineering might be a useful approach to control FMF and other rheumatic diseases, for example, via correction of the altered signalling pathways, production of metabolites with drug-like activities or anti-inflammatory molecules 4. The utility of this strategy will probably depend on the specific role of the microbiome in the complex interplay of genetics, environment and immunity at different stages of a particular disease.…”
supporting
confidence: 84%
“…These and previous studies in spondyloarthritis and rheumatoid arthritis reflect the growing interest of researchers to the role of the gut microbiome in shaping local and systemic immune responses and in pathogenesis of various rheumatic diseases 3. We agree with Deshayes et al that in the future microbiome engineering might be a useful approach to control FMF and other rheumatic diseases, for example, via correction of the altered signalling pathways, production of metabolites with drug-like activities or anti-inflammatory molecules 4. The utility of this strategy will probably depend on the specific role of the microbiome in the complex interplay of genetics, environment and immunity at different stages of a particular disease.…”
supporting
confidence: 84%
“…An increasing number of studies investigating probiotics have been performed in recent years. Lactobacillus is one of the probiotics present in the human intestine, which can improve intestinal microenvironment, regulate immunity and promote nutrient absorption (56)(57)(58)(59). Recent studies have demonstrated that probiotics also have a role in regulating abnormal brain activity (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…According to this study, the interaction of vital functions with the microbial pattern is the cause that leads to the appearance of pathologies that have no clear resolution in the medical field [48]. New types of drugs/supplements, with a clear direction toward pharmaceutical probiotics and prebiotic formulas, are seen as the solution to the physiological impairments that have arisen due to dysbiosis [62]. Increasing the number of strains is an alternative to the well known probiotics based on the species of the genera Lactobacillus, Bifidobacterium, and/or Streptococcus [48], although only the introduction of new strains cannot guarantee microbiota modulation over a period of time.…”
Section: Predictive Microbiota Responsementioning
confidence: 99%